Advanced Diagnostic Approaches for Necrotrophic Fungal Pathogens of Temperate Legumes With a Focus on Botrytis spp. - Bilkiss, Marzia; Shiddiky, Muhammad J. A.; Ford, Rebecca (Frontiers in Microbiology, 2019)
Plant pathogens reduce global crop productivity by up to 40% per annum, causing enormous economic loss and potential environmental effects from chemical management practices. Thus, early diagnosis and quantitation of the causal pathogen species for accurate and timely disease control is crucial. In particular, Botrytis Grey Mould (BGM), caused by Botrytis cinerea and Botrytis fabae, can seriously impact production of temperate grain legumes separately or within a complex. Accordingly, several immunogenic and molecular probe-type protocols have been developed for their diagnosis, but with varying levels of species-specificity, sensitivity and consequent usefulness within the paddock. To substantially improve speed, accuracy and sensitivity, advanced nanoparticle-based approaches have been developed. These novel nanotechnology methods have made enormous impact towards disease diagnosis in the medical sciences, and offer potential for transformational change within the field of plant pathology and disease management, at the point-of care and in the paddock. Here we review several recently developed diagnostic tools that build on traditional approaches and are available for Botrytis sp. diagnostics applications. We then identify the specific gaps in knowledge and current tool limitations and propose the research required to create nano-diagnostics to discriminate and quantify the BGM casual agents of Botrytis cinerea and Botrytis fabae on temperate grain legumes.